Demonic possession and lived religion in later Medieval Europe - Katajala-Peltomaa, Sari (Oxford studies in medieval European history, 2020)
Covering Western Europe (c. 1240-1450) and drawing upon a rich body of sources, this volume analyses how lay people understood the phenomenon of demonic presence and possession and used it to identify and unravel problems in their lives.